A Corpus Based Study on English Synonyms: Babble, Blather, Chatter, Gibber, Jabber and Prattle - Mohammad AlAmro (International Journal of Social Sciences & Educational Studies, 2019)
This paper examines in detail the six English words: babble, blather, gibber, jabber, prattle and chatter. While at first glance these words appear to have very similar meanings, and indeed can appear as synonyms of one another, each encompasses a different gradient of meaning. This paper describes the semantic usage and different senses of connotation that belong to these six words and also examines the lexical category of the word and how this can affect its meaning. The framework of the semantic description was laid through the comparison of the definitions of these words from several major dictionaries. This framework is refined through the use of the online corpus collection: Corpus of Contemporary American English (COCA). Many sample of each word have been collected and the collocations and contexts wherein they were found are examined in order to ascertain different shades of meaning.